Banyuwangi TV Media Convergence In Broadcasting Local Cultural Content In The Digital Media Era - Wahyu Agus Triyono; Denik Iswardani Witarti (Publikasi Indonesia, 2023)
The development of information and communication technology causes electronic media to start following technological developments related to a shift in media consumption patterns to online media such as the internet, television streaming and information that can be accessed via the internet. The number of internet users that is growing so rapidly is increasing along with the development of variations in internet-based communication media. Its use that is so easy and can be accessed anywhere is an option for most people. This study aims to determine the convergence of Banyuwangi TV media in broadcasting local cultural content in the digital media era. This qualitative descriptive research uses a case study approach, where the researcher identifies and analyzes a specific issue. Data were obtained from interviews with sources, books, articles, and other related literature. Using the concept of media convergence from Henry Jenkins, the results of this study indicate that Banyuwangi TV adopts three types of media convergence that are related to each other: a) technological convergence by managing online media in the form of websites (www.banyuwangi.tv) and youtube and being present in the media.